Elijah of Buxton [compact disc, unabridged] - Curtis, Christopher Paul (Random House/Listening Library, 2008)
In 1859, eleven-year-old Elijah Freeman, the first free-born child in Buxton, Canada, which is a haven for slaves fleeing the American south, uses his wits and skills to try to bring to justice the lying preacher who has stolen money that was to be used to buy a family's freedom.